Identification of gallbladder cancer by direct near-infrared measurement of deuterated chloroform-extracted organic phase from human bile - Kim, Yunjung; Jang, Eunjin; Hyun Shin, Ji; Kim, Min; Choi, Dongho; Chung, Hoeil (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2023)
[Display omitted] •A direct NIR measurement of organic phase extracted from human bile was demonstrated.•This scheme was to simply identify gallbladder (GB) cancer against other hepatobiliary diseases.•CDCl3 was used as an extraction medium for solvent interference-free NIR measurement.•The peak intensities of the GB cancer samples were lower than those of the other diseases.•The differences were statistically significant with a confidence interval greater than 99.0%. A simple near-infrared (NIR) spectroscopic scheme enabling direct measurement of organic phase extracted from human bile with no spectral interference from the extraction solvent was demonstrated for identification of gallbladder (GB) cancer. This scheme is used to recognize the different lipid contents in bile samples from GB cancer patients using NIR spectroscopy for disease identification. To this end, the extraction solvent should provide an absorption-free NIR region to observe peaks of related metabolite. For this purpose, deuterated chloroform (CDCl3) is uniquely suited as an extraction medium because it has few absorption peaks in the 4380–4100 cm−1 range, where intense peaks for lipids and cholesterol are located. This exploratory study used 37 bile samples (obtained from five normal subjects and nine GB polyp, 11 gallstone, six hepatocellular carcinoma (HCC), and six GB cancer patients). The transmission NIR spectra of the organic phases extracted using CDCl3 in a commercial glass vial were directly measured. The peak intensities of the GB cancer samples were lower than those of the other samples, and the differences were statistically significant, with a confidence interval greater than 99.0%. The lower lipid and cholesterol contents in the organic phases of the GB cancer samples were effectively identified in the corresponding NIR spectra. Therefore, the proposed NIR scheme is simpler and faster than the previous infrared (IR) measurement approach that requires solvent drying to highlight the buried metabolite peaks under a solvent absorption band.